Interaction between genotypes, environment and season (G x E x S) on anthocyanin corn in lowland zone of Indonesia. (May 2018) - Yasin H G, M; Isnaeni, M; Faesal,; Azrai, M
Abstract: Interaction between genotypes (G), environment (E) and season (S) on anthocyanin corn has been studied under lowland zone in Indonesia. The experiment were conducted using Randomized Complete Block Design (RCBD) based on location namely Maros, Bajeng, and Polman with three replications. Ten populations of open pollinated variety (OPV) of anthocyanins purple corn included checks were used in two planting seasons (dry and rainy) in 2015/2016. The objective of the experiment is to determine which of the population is stable and has high yield to be promoted as candidate for new OPV varieties. Genotypes were planted in four rows of 5.0 m length, spacing of 75 cm x 20 cm, one plant per hill, and applied with Urea, Ponska (300 and 200 kg Ha -1 ). Population was then selected by t test in model Yij =µ+βi Ij +δij, i≠j (Y: yield, µ: mean, β: regression coefficient, I: environmental index, δ: deviation from regression), and stability parameter bi =ΣYi Ij /I 2 j . The results show that there was a significant interaction of GxExS on PMU(S1).Synth.F.C1 and PPU(S1).F.C1 with yield ranging between 6 .70-8.48 t ha -1 and grain potential found in the locations of Maros and Bajeng in the rainy season. Content of anthocyanins were between 37.15 and 51.92 µg per 100 g sample.